(untitled) (Fiep Bulletin - online, 2011)
Descriptive exploratory study, developed in the emergency service of Hospital Monsenhor Walfredo Gurgel, with the objective of identifying factors that contribute with occupational violence against health professionals in the emergency service. The sample consisted of 124 physicians, 26 nurses and 95 nursing assistants/technicians, with data collected from April to May 2009. In order to analyze risk factors, we divided them in three groups: users, health professionals and structural organizational factors. In this sense, companions stand out as the main risk factor in the users group, being referred to by 212 professionals (86.53%). Among factors related to health professionals, the management staff was considered a risk factor by 58 professionals (23.67%). As for the structural and organizational factors group, inadequate physical structure was considered as a factor by 161 professionals (73.06%). Given that, based on the results in this study, we identify that inter-related measures aimed at the users, the health staff and structural organizational issues must be developed, since many factors are interlinked.